1999
DOI: 10.1002/lt.500050510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high donor serum sodium levels on early postoperative graft function in human liver transplantation: Effect of correction of donor hypernatremia

Abstract: Donor hypernatremia was reported to cause postoperative graft dysfunction in human orthotopic liver transplantation (OLT). However, the effects of the correction of donor hypernatremia before organ procurement have not been confirmed. The aim of this study is to determine whether donor hypernatremia is associated with early graft dysfunction after OLT and to determine the effect of the correction of donor hypernatremia. One hundred eighty-one consecutive OLTs performed between May 1997 and July 1998 were enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 28 publications
2
87
0
6
Order By: Relevance
“…In fact, allograft function from donors whose serum sodium was corrected to levels below 155 mEq/mL was comparable to those organs taken from normonatremic donors. 1 On the other hand, in the study by Londono et al, 5 the authors showed that recipient hyponatremia (serum sodium Ͻ 130 mEq/mL) reduced 3-month survival following OLT. From these observations, one can infer that both the donor sodium level at the time of organ procurement and the recipient serum sodium level at the time of transplantation can significantly impact post-OLT outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, allograft function from donors whose serum sodium was corrected to levels below 155 mEq/mL was comparable to those organs taken from normonatremic donors. 1 On the other hand, in the study by Londono et al, 5 the authors showed that recipient hyponatremia (serum sodium Ͻ 130 mEq/mL) reduced 3-month survival following OLT. From these observations, one can infer that both the donor sodium level at the time of organ procurement and the recipient serum sodium level at the time of transplantation can significantly impact post-OLT outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Idade do doador e hipernatremia está relacionada à alta mortalidade pós-operatória, mas novamente, os estudos publicados são conflitantes 23 . Não existe consenso sobre a idade do doador que comprometeria a função do enxerto.…”
Section: Discussionunclassified
“…Donors with serum sodium levels [ 155 mEqÁL -1 showed a significantly increased rate of early graft loss, while those with corrected serum sodium levels did not show such an increased rate of early graft loss. 61 The hypernatremia in brain death should be considered a hypovolemic state. If serum sodium levels persist [ 155 mEqÁL -1 following adequate volume resuscitation, the authors suggest infusion of a hypotonic solution, such as 0.45% NaCl (77 mEqÁL -1 ), as a maintenance fluid.…”
Section: Pulmonarymentioning
confidence: 99%